PELAKSANAAN INVENTORYPERALATAN DI BAR PADA RESTORAN SUSHI TEI PLAZA MANHATTAN MEDAN - Nirwaty Tarigan; Tambunan, Lyandru Togu Mulia; Rapepdi, Dikarpio Prahara (Akademi Pariwisata Darma Agung, 2023)
The equipment used by bartenders is very important and useful for smoothing operational activities at the bar so that there are no problems during operations. This research aims to determine the equipment available and used at the bar. Carrying out an inventory of the number of equipment and knowing the role of the supervisor regarding the equipment in the bar area. The research method used by the author is qualitative data, namely by observing the research object directly by collecting data on the bar. From the research results, it was concluded that there were still deficiencies in the bar at the Sushi Tei Manhattan Medan Restaurant. These deficiencies include a lack of equipment needed in the bar for the smooth running of ongoing operations, the implementation of equipment (inventory) calculations, and the role of the supervisor which has not been carried out properly and correctly. The suggestions that can be used as input and consideration are to immediately equip the bartender with the equipment needed so as not to hamper the smooth running of ongoing operations, to frequently carry out equipment counts at the bar, and for supervisors to check the number of equipment in the bar more often. to reduce the occurrence of loss and damage to equipment at the bar.